Managerial Ownership Analysis of Corporate Values in Real Estate Companies in Indonesia Stock Exchange - nurwahidah, nurwahidah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
This study aims to determine how much influence the Managerial Ownership (X) on Firm Value (y) in real estate companies on the Indonesia Stock Exchange The method used in this research is to use a causal associative research method with a quantitative (statistical) approach. with the sampling technique used was purposive sampling and obtained a sample of 10 real estate companies that fit the criteria and research objectives for the 2014-2018 research period. The data collection method used in this study was through a Sample Survey by collecting data from books, records or documents in the form of journals or various forms of periodic publications such as reports and references related to Real Estate companies on the Indonesia Stock Exchange which were sampled and the problem under study.The data analysis technique in this study was linear regression using SPSS ver.24 software with a significance level of 0.05 percent. The results showed that managerial ownership partially had a negative and significant effect on firm value, with a significance value of 0,000 <0,05.